Monoclonal antibodies as analgesia of chronic low back pain: a systematic review and meta-analysis of efficacy and safety - Nobel Budiputra; Charista Lydia Budiputri; Michelle Patricia Muljono (Анналы клинической и экспериментальной неврологии)
Introduction. Monoclonal antibodies (mAb) emerged as a possible option in addressing the partial response to current treatment modalities in chronic low back pain (CLBP).